PENDAMPINGAN MODIFIKASI KEMASAN DAN RASA PADA KERUPUK IKAN PAYUS DI DESA PONTANG SERANG - Andi Hasryningsih Asfar; Edwin Gunadi; Lisa Reftiana; Annisa Utami; Sadam Adriansyah (STAI Darul Qalam Tangerang, 2022)
Pontang is one of the areas in Serang Regency, Banten Province. One of the distinctive features of Pontang is the Payus fish cracker. Payus fish crackers are crackers made from payus fish. The reason for the insignificant sale of Payus Fish Crackers is that the packaging of Payus Fish Crackers is still simple and the taste is one variant. The research was conducted using direct interviews and literature studies with business owners of payus fish crackers.Based on the results of the existing analysis, it is necessary to develop Payus fish cracker products to update labels, flavors, packaging that are more attractive and the role of marketing to attract consumer interest